Structural detailing in timber : a comparative study of international codes and practices - Bangash, M. Y. H. (Whittles ; Distributed in North America by CRC, 2009)
"This manual provides practical and up-to-date information on various aspects of timber construction and covers the fundamentals of drawing and drafting practices, connections and fastening and structural detailing of various timber elements. The types of structures covered represent the bulk of the typical fabricator's work in timber structures such as buildings, bridges, grid-works, shells, folded plates, etc. Some examples of timber detailing in CAD form are also included. The book is liberally illustrated with line drawings and many detailing sheets, the latter linked to international codes of practice."--Back cover.